Sharon Ris: "The Reality is the Present Tense" - Robinson, Jack (Studies in Canadian Literature, 1991)
Ris's fiction is concerned with how journeys of the imagination and the spirit, with their existential and metaphysical implications, redefine literary conventions and cultural myths of truth and reality. Her first novel, The True Story of Ida Johnson, is a novel about ideas, expressed in a rural, realist fashion. Riis says that a good book "pulls you inside another world, the characters become part of you forever." In Midnight Twilight Tourist Zone, Ris describes how her characters' "shared dreams are like bleed-throughs into other realities and all of these people are related in different constellations." In addition to two novels, Riis has written several film and television scripts: she says that when writing for film, you have to think visually and keep the story simple.